Religious Moderation Education: An Interpretative Phenomenological Analysis on Identity Reconstruction in Polite Islamic Literacy Ambassadors - Guritno, Sari Asih; Lessy, Zulkipli; Ahmad, Mokbul Morshed (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – Literasi Islam Santun’s or LISAN’s program stress the necessity for religious moderation education around State Universities. Millennials are the main target of this program. It is clearly seen that intolerant values on social media considerably affect their personal and social identity so that it further requires an understanding of how to establish identity reconstruction in millennials who become the ambassadors of LISAN. The purpose of this research is to find out how self-and social identity reconstruction in students who become LISAN Ambassadors. Design/methods/approach – The research is qualitative research with interpretative phenomenological analysis (IPA) approach. The data source of this study is on millennials who participated in the ambassadors of LISAN, totaling seven people.The data source of this study is on millennials who participated in the ambassadors of LISAN. Data collection techniques were conducted through interviews and collection of essay writings by research subjects. Data analysis techniques use reduction, data presentation, and data interpretation. Findings – The results of this study showed that according to analysis of two main superordinate and the five subordinate themes presented by seven informants, it can be concluded that reconstruction of the informants’ identity as the ambassador of LISAN involves important aspects in the process of individual development, namely cognitive, emotional and behavioral. Thus, this gives rise to a new identity that makes them become individuals as the LISAN’s ambassadors who have new behaviors that are more moderate and tolerant. Research limitation – The study has the limitation as it covers only small number of respondents in one locus. Future research is suggested to investigate a wide range of respondents. Originality/value – The research contributes to motivate academics for promoting moderation in practicing faith and religion in the milieu of State University.